Evaluation of Resin Zein Films Containing SugarPlasticizers by Permeability and Atomic Force Microscopy Analysis: Surface evaluation of resin zein films - Ghanbarzadeha, Babak; Oromiehi, Abdorasul; Razmi-Rad, Elhameh (Iranian Journal of Pharmaceutical Sciences, 2008)
Zein is one of the best biopolymer for edible film making and sugars are naturalplasticizers for biopolymers. In this research, sugars (fructose, galactose andglucose) at three levels (0.5, 0.7, 1 g/g of zein) were used as plasticizers for zeinprotein films and their water vapor permeability (WVP), oxygen permeability (OP)and atomic force microscopy (AFM) topography were studied. The pure zein filmshad the highest WVPand adding sugars to 0.7 g/g of zein decreased WVPof thefilms. In comparison among different zein films, those plasticized by galactose andfructose had the highest and lowest barrier properties, respectively. The zein filmswithout plasticizer had low OPand increasing plasticizers to 0.5 g/g of zeindecreased OPvalues in all samples. The films containing galactose and fructose hadthe lowest and highest OP, respectively. AFM images were used to evaluate surfacetopography (a qualitative parameter) and roughness (a quantitative parameter) ofthe zein films. The films plasticized by fructose had smoother surface and lowerroughness than the other films. Interrelation between WVP, OPand the roughnessof zein films were not observed.